2013
DOI: 10.1063/1.4813855
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative electron transfer dynamics in mixed valence dimers: Microscopic approach to the solid state problem

Abstract: We propose a microscopic analytical approach to the description of the low-temperature dissipative intracluster electron transfer dynamics in centrosymmetric one-electron mixed-valence (MV) dimers. The dissipative system (bath) is supposed to consist of the acoustic phonons of the crystal surrounding that are coupled to the delocalized electron(s) of a MV dimer. Although the concept of the bath is the spin-boson model is more generic, the present consideration is relevant, for example, to a MV bi-center impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In this work, we model the dissipative dynamics based on the Bloch-Redfield approach, [65][66][67] which has proven its usefulness in various applications. [68][69][70][71] It is based not only on a weak coupling assumption, but also on the Markov approximation, valid when the bath correlation functions decay rapidly as compared to the typical system timescales. Note that this constraint can be overcome by non-Markovian methods, [72][73][74][75] and the vibronic Hamiltonian developed in this work could in the future be directly used within this framework.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we model the dissipative dynamics based on the Bloch-Redfield approach, [65][66][67] which has proven its usefulness in various applications. [68][69][70][71] It is based not only on a weak coupling assumption, but also on the Markov approximation, valid when the bath correlation functions decay rapidly as compared to the typical system timescales. Note that this constraint can be overcome by non-Markovian methods, [72][73][74][75] and the vibronic Hamiltonian developed in this work could in the future be directly used within this framework.…”
Section: Introductionmentioning
confidence: 99%
“…As an advantageous system, one can mention the MV vanadium dimer, formulated as [(PY 5 Me 2 ) 2 V 2 (μ-5,6-dimethylbenzimidazolate)]­(PF 6 ) 4 , which has been reported by Long et al The imidazolate is a compact, symmetric, and conjugated bridging ligand, for which manipulation of the character of the frontier orbitals is available, and therefore, the double exchange can be tuned by chemical means (see details in ref ). In this MV dinuclear vanadium­(III)–vanadium­(II) ( d 2 – d 3 ) complex, the double exchange stabilizes the high-spin state with S = 5/2, with respect to the lower-spin states with S = 3/2 and S = 1/2, which are excited states lying around 100 cm –1 above the ferromagnetic ground state . In view of our study, it is important that the role of the vibronic coupling has been underlined.…”
Section: Discussion Of the Systems And Parametersmentioning
confidence: 78%
“…In this MV dinuclear vanadium(III)−vanadium(II) (d 2 −d 3 ) complex, the double exchange stabilizes the high-spin state with S = 5/2, with respect to the lower-spin states with S = 3/2 and S = 1/2, which are excited states lying around 100 cm −1 above the ferromagnetic ground state. 34 In view of our study, it is important that the role of the vibronic coupling has been underlined. It was indicated that this is a gap, which is actually reduced by the vibronic coupling with respect to the double exchange splitting expected in the electronic spectrum.…”
Section: Discussion Of the Systems And Parametersmentioning
confidence: 99%
See 2 more Smart Citations